Angola Agriculture Support Policy Review : Realigning Agriculture Support Policies and Programs - World Bank (World Bank, Washington, DC, 2021)
This report assesses agriculture policy support estimates in Angola. These estimates represent the monetary value assigned to different agriculture support policies and programs using the OECD methodology for the years 2018–2019. The advantages of using the OECD methodology are that: (a) it provides a systematic and integrated view of agriculture support policies and programs (not limited to the more traditional public expenditure reviews or rate of protection); (b) given the large number of countries using this same methodology to measure support estimates, an immediate benchmarking is possible across a large set of comparators; and (c) the methodology is simple and can be integrated into the agriculture public policy analysis conducted by the Government and other stakeholders. The methodology also has some disadvantages and limitations, mainly: (a) while it quantifies the level of support provided to producers and consumers, it does not further disaggregate support received by type of agricultural producers (small-scale, large-scale; family farm, commercial) or consumers; (b) since the estimates are based on the monetary value of budget and price support, non-monetary support, like the quality of policies, is not captured (e.g., the methodology is able to identify how much policy/program support is invested in land administration efforts, but unable to qualify the impact (quality) of those policies/programs). This assessment aims to support the Angolan Government in reviewing its agriculture policies and programs, in particular to: (a) provide new estimates and a new approach to assess sector support for policy decision-making; (b) allow for benchmarking agriculture support policies with a large global database of countries using the same estimate methodology; and (c) help kickstart a policy dialogue on realigning agriculture policies and programs in Angola towards greater sector competitiveness and fast economic recovery from the coronavirus disease 2019 (COVID-19) pandemic, increased food security and nutrition outcomes, and climate sustainability through a build back better approach.